The pondok & madrasah in Patani - Hasan Madmarn (Monograph (Universiti Kebangsaan Malaysia. Institut Bahasa, Kesusasteraan dan Kebudayaan Melayu), 1999)
Patani, a southern border province of Thailand was once the center of Islamic education and earned the title "cradle of Islam" for the Malay Muslim World. Patani has preserved a unique religious, cultural character and institution which could not be found in the region. This town, with its well-known pondok and its learned tok guru attracts Muslims from the four southern provinces. The pondok being the center of traditional Islamic education of the Muslims in Thailand became the focal point of attention by the Thai Government in the past three decades. During the process of education reform the pondok institution was first changed into the madrasah before transforming into the Islamic private schools. The government strives to incorporate the Thai language and culture into the Islamic religious schools. The outcome of the government's effort shows that the students of the Islamic private schools now master Thai, Malay and Arabic.